THE INNOVATIVE TRENDS IN THE METHODOLOGY OF PHYSICAL EDUCATION OF CHILDREN IN THE AGE OF 5-6 - Petrenko, Hennadij (Journal of Education, Health and Sport, 2015)
Petrenko Hennadij. The innovative trends in the methodology of physical education of children in the age of 5-6. Journal of Education, Health and Sport. 2015;5(10):306-317. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34306 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A306-317 https://pbn.nauka.gov.pl/works/673013 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 25.10.2015. THE INNOVATIVE TRENDS IN THE METHODOLOGY OF PHYSICAL EDUCATION OF CHILDREN IN THE AGE OF 5-6 Hennadij Petrenko National University of Physical Education and Sport of Ukraine The article deals with the substantiation of the integrated lessons with the usage of multifunctional equipment in physical education of senior preschool children. It is established that the improvement of efficiency of motor skills development and the emotional coloring of physical training lessons for senior preschool children should be achieved due to the sport exercises done alongside with musical accompaniment, various equipment. All this has a positive impact on improving the overall health condition and removal of child’s functional adaptation systems tension. Keywords: senior preschool children, integrated lesson, sports-oriented physical education, musical accompaniment, polypropylene equipment.